Border Management Modernization - McLinden, Gerard; Fanta, Enrique; Widdowson, David; Doyle, Tom (World Bank, 2012)
This book provides border management policymakers and reformers with a broad survey of key developments in and principles for improving trade facilitation through better border management, including practical advice on particular issues. In contrast to the traditional border management reform agenda, with its focus on improving customs operations, this book addresses both customs reform and areas well beyond customs-a significant broadening of scope. The book thus presents a new, more comprehensive approach to trade facilitation through border management reform: an approach that embraces a much wider, 'whole of government' perspective. The objective of this book is to summarize and provide guidance on what constitutes good practices in border management-looking beyond customs clearance. The contributions to the volume make clear that there are no simple or universally applicable solutions. Instead, the aim is to provide a range of general guidelines that can be used to better understand the complex border management environment and the interdependencies and interrelationships that collectively need to be addressed to secure meaningful change and improvement.